Agrammaticalized mono- and polysynonymic constructions in the novels of San-Antonio - Lepetiukha, Anastasiia (Romanica Olomucensia, 2024)
In this research, mono- and polysynonymic constructions are considered as transforms of a virtual primary syntagm or proposition which are actualised in the form of grammaticalised (conventional in language and discourse) and typical (non-conventional in language and conventional in discourse) and atypical (non-conventional in language and in discourse) agrammaticalised co(n)textually pertinent preferential options. In grammaticalised utterances, expression prevails over expressiveness, while in agrammaticalised structures, expressiveness predominates over expression. In this article, the procedure of inverse reconstruction (discourse extrightarrow language) of the primary structure is used. An ``alternative'' linguistic experiment is conducted, consisting of the replacement of a synonymic utterance by another in a discursive fragment that is analysed in order to justify the co(n)textual pertinence of the preferential option. During the research, typical and atypical agrammaticalised mono- and polypredicative quantitatively equacomponential, redundant, and compressed structures and bi and polysynonymic bi- and polyagrammaticalised preferential options (typical/atypical agrammatisation + typical/atypical agrammatisation) at the level of a syntagm or utterance are distinguished. It is revealed that in the novels of San-Antonio, monosynonymic atypical agrammaticalised utterances predominate. It is concluded that the actualisation of typical and atypical mono- and polypredicative mono- and polysynonymic agrammaticalised constructions, the result of the transformation of morphologically, syntactically and semantically balanced primary structures, where the predominance of expressiveness over expression sometimes leads to dissyntaxy, is one of the idiostylistic features of San-Antonio, who uses ludic strategies to facilitate or complicate the identification of his communicative intention and the interpretation of the information by the reader.
Keywords: ``alternative'' linguistic experiment; bi- and polyagrammatisation; co(n)textual pertinence; primary structure; typical and atypical agrammaticalised mono- and polysynonymic constructions